The effect of personality traits and parental attitudes on treatment in children and adolescents: a 6-month follow-up study - İlnem, Müjen (The European Research Journal, 2022)
Objectives: This study aims to examine the effects of personality traits and parental attitudes on the change of emotional and behavioral problems in children and adolescents with mental disorders receiving outpatient treatment during the six months. Methods: In the study, 233 individuals between the ages of 7-17 who applied to the Child Psychiatry Outpatient Clinic of a private hospital in Istanbul between September 2015 and September 2017 and who had psychiatric disorders regarding DSM-V diagnostic criteria were evaluated before treatment with the Sociodemographic Data Form, Strengths and Difficulties Questionnaire (SDQ), Quick Big Five Personality Test (QBFPT), and Parental Attitude Scale (PAS). Emotional and behavioral problems of children and adolescents who were followed up for psychiatric treatment were evaluated by SDQ at the first, third, and sixth months. Results: According to the Pearson Correlation Analysis, it was found that the SDQ total scores of children and adolescents in the pre-treatment period were statistically significantly positively correlated with the Democratic Attitude subscale scores (r = 0.129, p = 0.049). Considering the QBFPT and PAS sub-dimension scores in ANCOVA analyzes, the change in the SDQ total scores before and after treatment was statistically significant (p < 0.05), and Democratic Attitude subscale scores (F = 2.70, p = 0.048) and Emotional Stability subscale scores (F = 3.27, p = 0.023) had statistically significant effects on this change. Conclusions: In children and adolescents with mental disorders, focusing on democratic attitudes and personality traits associated with emotional stability may help reduce emotional and behavioral problems during treatment.